Nguyen Khac Huynh [Vietnam, Diplomat] - Huynh, Nguyen Khac (Institutional Knowledge at Singapore Management University, 2015)
Nguyen Khac Huynh was a key member of the 1968-1973 Paris Peace Talks on the Vietnam War. He talks to DNA about how Vietnam managed to negotiate a settlement that saw the US withdraw from South Vietnam, despite being a weaker power. Hear also the long-time diplomat, soldier and academic's thoughts on the qualities of a good leader.